Cardiac magnetic resonance characterization and prediction of left ventricular thrombus after ST-segment elevation myocardial infarction. (3rd October 2022) - Bertolin-Boronat, C; Marcos Garces, V; Perez, N; Gavara, J; Lopez-Lereu, M P; Monmeneu, J V; Rios-Navarro, C; De Dios, E; Merenciano-Gonzalez, H; Gabaldon-Perez, A; Iraola Viana, D; Bonanad, C; et al.
Abstract: Background: Left ventricular thrombus (LVTh) is an uncommon yet serious complication after ST-segment elevation myocardial infarction (STEMI). Late gadolinium enhancement (LGE) sequences in cardiac magnetic resonance (CMR) imaging allows for accurate detection of LVTh. However, the implications of CMR to predict and characterize LVTh occurrence is this population is unclear. Purpose: We aim to characterize the incidence, outcomes, and predictors of LVTh after STEMI by CMR imaging. Methods: Our registry comprised 455 patients admitted for a first reperfused STEMI in our university hospital. Baseline characteristics were recorded. All patients underwent early (1-week) and late (6-month) CMR. Left ventricular ejection fraction (LVEF, %), infarct size (% of left ventricular mass) and microvascular obstruction (MVO, number of segments) were measured. LGE sequences were used to analyze the presence of LVTh. Patients with LVTh at 6-month CMR underwent an additional CMR 1 year after admission. Univariate and multivariate comparisons were performed to study the ocurrence of LVTh in the first 6 months after STEMI. Results: Mean age was 58.24±11.69 years, most patients were male (82.6%) and anterior infarction occurred in more than half of the cohort (52.7%). LVTh was detected in 36 (7.9%) patients in the first 6 months after STEMI. Anticoagulation was initiated in all cases. Of these, 27 patients had LVTh at early (1-week) CMR, but 9 had LVTh at late (6-month) CMR with no prior evidence of LVTh at early CMR. A total of 6 patients had persisting LVTh at 1-year CMR (37.5% of patients with 6-month LVTh). In multivariable analysis, anterior infarction (HR 6.6 [1.91–22.83], p<0.001) and 1-week CMR-LVEF (HR 0.97 [0.93–0.99], p=0.04) and MVO (HR 1.19 [1.02–1.39], p=0.03) independently predicted the occurrence of LVTh in the first 6 months after STEMI. We computed a risk score of LVTh assigning 1 point to each of these variables (anterior infarction, CMR-LVEF <50% and MVO >3.5 segments), which allowed us to stratify the risk of LVTh in the first 6 months after STEMI (0.6% if 0 points, 3.8% if 1 point, 14.4% if 2 points, and 31.2% if 3 points). Conclusions: CMR imaging soon after STEMI can contribute relevant prognostic value regarding LVTh occurrence after the acute event. Patients with anterior infarction, LVEF <50% and MVO in >3.5 segments at early (1-week) CMR have the highest risk of LVTh in the first 6 months after STEMI. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Instituto de Salud Carlos III and "Fondos Europeos de Desarrollo Regional FEDER" and Conselleria de Educaciόn – Generalitat Valenciana.